Mother's employment and fertility in Norway - Mette Gerster; Trude Lappegård (Statistics Norway, Research Department, 2010)
This paper concerns the effect of employment status on second- and third-birth intensities for Norwegian mothers in the period 1994-2002. Due to unobserved heterogeneity possibly affecting both the birth and the employment processes we employ a simultaneous equations approach for hazard models, originally suggested by Lillard (1993). Our results show that there is a slightly positive effect of currently being in employment on the second-birth intensity, whereas the third-birth intensity is larger for women who are currently non-employed, even when unobserved heterogeneity is taken into account. This suggests that even in a society such as the Norwegian in which there is a high compatibility between motherhood and labour market attachment there are still certain costs associated with childbearing and that this is taken into account by Norwegian women, in particular when it comes to the progression to third child.
Keywords: J01; J13; 330; Fertility; employment; family policy